Effects of a multilayer snow scheme on the global teleconnections of the Indian summer monsoon. (5th March 2019) - Sujith, K.; Saha, Subodh Kumar; Rai, Archana; Pokhrel, Samir; Chaudhari, Hemantkumar S.; Hazra, Anupam; Murtugudde, Raghu; Goswami, B. N.
Abstract : Eurasian snow is one of the slowly varying boundary forcings known to have significant influences on the mean and variability of the Indian summer monsoon rainfall (ISMR). A multilayer complex snow scheme, incorporated into the state‐of‐the‐art coupled Climate Forecast System version 2 (CFSv2) showed significant improvements in the simulation of mean ISMR, snow, and Northern Hemisphere surface and tropospheric temperature. Here we show that a realistic simulation of high‐latitude snow decreases the north–south temperature gradient, which in turn decreases the meridional transport of energy from the Equator to the Pole, consequently affecting the tropical sea surface temperature (SST) and air–sea interactions. The global teleconnections of the ISMR with SST and 2 m temperature over land are also improved considerably in association with improved simulation of the oceanic natural modes of variability. Our findings provide new insights for the relationship between the winter Eurasian snow and the following ISMR, namely that the same relationship may be understood through a framework of meridional atmospheric energy transport and its effects on the tropical air–sea interactions. The improvements in the global teleconnection in the modified version of CFSv2 may have implications in the ISMR predictability and prediction skill. Abstract : Global boreal summer (June to September) rainfall in mm/day. Climatological rainfall from (a) GPCP and (b) CFS_OSS. (c) Bias in CFS_OSS with respect to GPCP and (d) difference between the CFS_NSS and CFS_OSS.